A simple approach to modelling the soil water budget in cool temperate mineral topsoils. (May 2020) - Brand, Alison; Lilly, Allan; Smith, Jo
Abstract: A simple soil water budget model is introduced and evaluated against data collected at four sites at Gourdie, near Dundee, Scotland, during 2000, using both short-term (2000-only) and long-term (1961–2011) averaged climate data. The performance of the model is compared using five different pedotransfer function sets to derive parameters for cool temperate mineral soils. Simulated soil water values were significantly correlated with measurements for all pedotransfer functions and climate-terms. The minimum total error achieved between simulations and measurements for the best performing pedotransfer function was 19%, suggesting that predictions are accurate to within 20% of the average measurement. A low bias was observed in the simulations when compared to measured values, suggesting only a small systematic overestimate (2.8% of average measurement). Some model assumptions may have been invalidated where extreme events such as storms or anomalous dry spells were not captured in the monthly time-step led to small model errors. Graphical abstract: Precipitation input is partitioned into rain, P r a i n, snow, P s n o w, and after a lag, snow meltwater, S m e l t . V s and V F C represent the soil water contents at saturation and field capacity, respectively. Drainage consists of direct runoff (from impervious or sloping ground), V d r o, overland flow, V O F, subsurface lateral flow, V S L F, and subsurface vertical flow, V S V F . The soil water level lies within: Box A, V O F = V S L F = V S V F = 0 ; or Box B, V O F = 0 . Image 1 Highlights: Evaluates a tool to predict soil water budgets in the soil/plant system. Uses existing process-based models from scientific literature. Driven by commonly available meteorological data and soil descriptions. Five PTFs compared: Hollis et al. (2014) is best suited to Scottish soils. Easily adaptable for different uses by other researchers.